1984
DOI: 10.1530/jrf.0.0720467
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against epididymal glycoproteins block fertilizing ability in rat

Abstract: Antiserum against rat androgen-dependent secretory epididymal protein DE (raised in rabbit) was added to suspensions of rat spermatozoa from the cauda epididymidis which were used for artificial insemination. While control spermatozoa fertilized 41.6% of oocytes, those exposed to antiserum to protein DE fertilized only 6.6% (P less than 0.01). An equal amount of normal rabbit serum (NRS) did not cause inhibition (33.1%). To study the entry of antibodies into the epididymis, caudal tubules were cultured for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…This suggests that ADAMs could function in redundant roles, consistent with the fact that ADAMs have similar adhesionmediating motifs to interact with integrins via their disintegrin domain (D in the diagram) [124,[126][127][128]. Cysteine-rich Secretory Protein 1 was implicated in sperm-oocyte fusion by antibody studies in the 1980s [129,130], and the Crisp1 knockout was recently reported. Sperm from Crisp1 -/-males show a modest decrease in sperm-oocyte fusion in in vitro fertilization assays, although male fertility appears normal [131].…”
Section: Gamete Membrane Fusion and The Oocyte-to-embryo Transitionmentioning
confidence: 70%
“…This suggests that ADAMs could function in redundant roles, consistent with the fact that ADAMs have similar adhesionmediating motifs to interact with integrins via their disintegrin domain (D in the diagram) [124,[126][127][128]. Cysteine-rich Secretory Protein 1 was implicated in sperm-oocyte fusion by antibody studies in the 1980s [129,130], and the Crisp1 knockout was recently reported. Sperm from Crisp1 -/-males show a modest decrease in sperm-oocyte fusion in in vitro fertilization assays, although male fertility appears normal [131].…”
Section: Gamete Membrane Fusion and The Oocyte-to-embryo Transitionmentioning
confidence: 70%
“…Before the acrosome reaction occurs, DE is localized on the dorsal region of the rat sperm acrosome and subsequently migrates to the equatorial segments, where sperm begins to fuse with an oocyte . Polyclonal anti-DE antibodies significantly prevented sperm from fusing with zona-free oocytes without changing either the mobility or binding ability of the sperm (Cuasnicu et al 1984). A purified DE protein could bind to the entire surface of oocytes except the region over the meiotic spindle, where sperm rarely fuse , suggesting that there is a receptor for DE on the surface of oocytes for promoting the sperm -oocyte fusion.…”
Section: De On Spermmentioning
confidence: 97%
“…Sperm coating glycoprotein is known to associate with the acrosomal region of spermatozoa after secretion from the epididymis [22]. Antibodies against the protein were able to block fertilization of an ovum [23], indicating a role for sperm coating glycoprotein in the penetration by spermatozoa of the extracellular matrix-like zona pellucida, which surrounds the ovum. A role of SGP28 in degradation of the extracellular matrix during neutrophil migration is possible and suggested by its localization in specific granules, where other matrix degradative enzymes are stored [1][2][3]5].…”
Section: -Ementioning
confidence: 99%